ASUHAN KESEHATAN GIGI DAN MULUT PADA TN.MA (21 TAHUN) DENGAN KASUS PEWARNAAN EKSTRINSIK (STAIN) DISERTAI KEBIASAAN MENGKONSUMSI KOPI DAN ROKOK DI KLINIK JURUSAN KESEHATAN GIGI KOTA BANDUNG - Azhar, Salsabilah Nur; Heriyanto, Yonan; Fatikhah, Nurul; Nurjanah, Neneng (Jurnal Terapi Gigi dan Mulut, 2024)
Tooth coloring or stain is a color that sticks to the surface of the teeth, usually due to the adhesion of food color, drink, or nicotine content which is the substance that produces tooth stain. This case occurred in Mr. MA who was 21 years old who had a habit of consuming coffee and cigarettes. The aim of this research is to determine the results of dental and oral health care for clients who have the habit of consuming coffee and cigarettes at the Dental Health Department clinic. This research method is a case report with the concept of dental and oral health care which consists of a process of assessment, diagnosis, planning, implementation and evaluation. This research involved examining Mr. MA using a medical record summary sheet. After carrying out the examination, the diagnosis stated that there were 5 basic human needs that were not met. The implementation carried out on clients is cleaning tooth stains, cleaning tartar, filling fissure sealants, counseling using the Chair Side Talk method and oral physiotherapy. The evaluation results show that there are 5 basic human needs that have been met, so the client's 8 basic human needs have been fully met.